Investigation of depth selective Raman spectroscopy on a layered synthetic prostate tissue model - Viknesh Shanmugam (2011)
This report presents a systematic study on the feasibility of using Raman spectroscopy to develop a depth selective technique for optical diagnosis on a layered tissue model. Raman spectroscopy is chosen because of the potential to make use of depth dependent optical signatures to derive an optical diagnosis. The study was split into 2 components, with the first component involving the how sensitive a Raman system can be with regards to the detection of prostate cancer tissue from healthy prostate tissue while the second component involves the demonstration of the concept of depth selective Raman measurements on a prostate tissue phantom. The success of this technique ultimately aims to make the biopsy process in cancer diagnosis minimally invasive. Agarose based bi-layer synthetic tissue phantoms were created mimicking the optical characteristics of human prostate tissue. 2 different Raman scatterers were used to identify and relate the significant peaks on the spectrograph to the respective layer. Urea at a concentration of 2M , was used as the Raman scatterer for the bottom layer with a fixed depth of 5000 µm. Rhodamine 6G (R6G) at a concentration of 10-3M, was the Raman scatterer used for the top layer of the phantom with variable depths at 400 µm, 800 µm,1200 µm and 1600 µm respectively. Results showed the best spectral separation between the top and bottom layers was achieved when the top layer depth was thinnest at 400 µm.